Ignaz Goldziher’s Contributions to the History of the Qur’an: His Motivations, Methodology, and a Critical Analysis of His Views - An Analytical Study - Abdul-Ali Hameed Al-Mayyah, Lect . Dr. Anwar (Basra studies journal, 2025)
This study explores the contributions of Hungarian orientalist Ignaz Goldziher to Qur’anic studies by analyzing his methodology, interpretations, and influence on Western scholarship. It focuses on his historical and linguistic approach to the Qur’an and highlights his reliance on philological and historical-critical methods to investigate the origin and development of the text. The research also examines the intellectual and religious backgrounds—such as Jewish traditions and Protestant theology—that shaped his critical perspective. By comparing Goldziher’s writings with classical and modern Islamic sources, the study reveals methodological inconsistencies and epistemological biases in his work. Ultimately, it calls for a nuanced critique of Orientalist discourse that goes beyond mere acceptance or rejection, emphasizing the need for scholarly approaches that interrogate the epistemic and ideological frameworks of such studies